Sejarah dan Pemanfaatan Gordang Sambilan dalam Adat Mandailing Natal - Sakinah Nasution; Laila Rohani; Franidya Purwaningtyas (Medan Resource Center, 2021)
This study aims to determine the history of Gordang Sambilan in Mandailing Natal and the development of Gordang Sambilan music from pre-Islamic until now. The benefit of this research can provide input and considerations for the management of the Mandailing Natal District Tourism and Culture Office. Cultural theory as material for this study. The anthropological approach used in this study because it examines the development of culture in historical studies. Historical methods such as source collection, verification, interpretation and history are used in this research with the form of qualitative research and carried out by using data collection techniques Focus Group Discussion (FGD). The research location is in Mandailing Natal Regency, especially in Panyabungan Mandailing Natal, Department of Tourism and Culture, and Education Office of Mandaling Natal Regency. The results of the study determine the history of the birth of a typical musical instrument from Mandailing Natal, namely the Gordang Sambilan, and its use in the traditional Mandailing Natal. Musical instruments with distinctive characteristics that have reached the immediate future and the developments that have been passed from pre-Islamic to the present are marked by changes in terms of making Gordang Sambilan and the basic materials are different but the meaning and sound that are issued remain the same.